Development of an electrochemical sensor nanoarray for hydrazine detection using a combinatorial approach - Baron, R; Sljukic, B; Salter, C; Crossley, A; Compton, R (2007)
The combinatorial screening of different metallic nanoparticles as electrocatalysts was investigated and efficiently applied for the detection of hydrazine. In a first step, glassy carbon microspheres decorated with metallic nanoparticles (Au, Pd, and Ag) were abrasively attached on the surface of a basal plane pyrolytic electrode giving a 'multi-metal' nanoarray. In a second step, electrodes modified with only one type of metallic nanoparticles allowed the identification of Pd as the unique catalytic material. In addition, a carbon-epoxy composite electrode loaded with the Pd nanoparticles was then constructed for a practical use. The carbon-epoxy composite nanoarray electrode was found to have excellent characteristics as for the sensing of hydrazine with a limit of detection of 2 μM. © 2007 Wiley-VCH Verlag GmbH and Co. KGaA.